Pesticide usage pattern for vegetable cultivation in Manmunai South & Eruvilpattu divisional secretariat Division of Batticaloa district, Sri Lanka - Sutharsan, S; Sivakumar, K; Srikrishnah, S (International Journal of Agricultural Research, Innovation and Technology, 2014)
Batticaloa, is a coastal district in Sri Lanka. Vegetables except up-country vegetables sold in Batticaloa District are mainly grown in villages. Manmunai South and Eruvilpattu divisional secretariat (DS) division is a predominantly vegetable cultivating area in the Batticaloa district. Farmers in this region use variety of synthetic pesticides to protect vegetables. Recently public concern related to health risks associated with pesticide residues has been increased, substantially. Therefore, a study was conducted to find out pesticide usage practices of farmers on vegetable cultivation in Manmunai South and Eruvilpattu DS division. Stratified random sampling method was used to select respondents for the survey and the collected data were analyzed statistically. It was observed that, the usage of pesticides was higher in the study area. Vegetable farmers use more than 14 Insecticides to control pest infestation. Farmers in the study area apply pesticides more frequently. Highly pesticide sprayed crop is Brinjal. About 66% of the Chilli producing farmers and 84% of the Brinjal producing farmers apply pesticide more than 22 times per cropping season. Around 90% of the farmers apply more than the recommended dosage and frequency of the pesticides. It was noticed that more than 89% of the farmers harvest the produce before the recommended pre harvest interval. It was found out that farmers in the study area are not following recommended pesticide usage practices. Hence, it is essential to educate the farmers on recommended pesticide usage practices, reduced usage of synthetic pesticides and use of organic farming practices to reduce the ill effects of synthetic pesticides. DOI: http://dx.doi.org/10.3329/ijarit.v4i1.21092 Int. J. Agril. Res. Innov. & Tech. 4 (1): 53-56, June, 2014